Exploring Meaning in Life by Thematic Analysis - Zainab Fatima; Zartashia Kynat Javaid; Mehram Altaf; Ayesha Tariq (Review Journal of Social Psychology & Social Works, 2025)
Meaning in life is a common phenomenon when pondering the validation of human existence. In this study, an attempt is made to discover the meaning in individuals’ lives, their experiences and the factors affecting them. It was a semi-structured interview method of data collection in qualitative research. Data was analyzed using thematic analysis. A sample was taken from 10 students aged 19 years and above. The participants were students in a public sector university. The main themes were assigning meaning, making sense of chaos, continuous journey or destination, perspectives on the impact of positive and negative aspects, religion, society, culture and universal or subjective. Subjective factors influenced the outcome of this research. Negative emotions encouraged and helped the researchers to find different ways. It is concluded that meaning in life is deeply rooted in the intersection of societal expectations, cultural traditions, and religious convictions. The implications of meaning in life are integral for achieving a balanced, fulfilling, and resilient existence. It also influences how we reflect on our past, appreciate the present and envision or hope for the future.